Constitutional and Siyasah Dusturiyah Review of Neglected Child Protection in Purwakarta - M Yahya Wahyudin; Rena Zulfaidah (Siyasah Dusturiyah: State Law Review, 2026)
The phenomenon of neglected children in Purwakarta Regency exposes a severe disconnect between the 1945 Constitution and actual regional protection practices. Utilizing an empirical approach, this study critically analyzes legal frameworks, direct field observations, and targeted interviews with local social agencies to evaluate regulatory implementation. Findings reveal acute institutional paralysis and ineffective bureaucratic synergy, reducing Regional Regulation Number Two of 2021 into a mere administrative text. Consequently, state interventions completely fail to address structural poverty and the rampant economic exploitation continuously orchestrated by organized street child mafias. To rectify this systemic failure, this research proposes integrating the interdisciplinary principles of Siyasah Dusturiyah and Maqashid Shariah. Operationalizing the ethical concepts of Hifdz al Ummah alongside established jurisprudential maxims strictly demands a transformative governance model. Substantively protecting marginalized youth directly requires dismantling these exploitative networks rather than merely enforcing superficial public order, thereby genuinely actualizing a fully constitutional regional protection environment today.